Charged-particle multiplicities in pp interactions at root s=900 GeV measured with the ATLAS detector at the LHC - Aad, G; Abat, E; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; et al. (ELSEVIER SCIENCE BV, 2010)
The first measurements from proton-proton collisions recorded with the ATLAS detector at the LHC are presented. Data were collected in December 2009 using a minimum-bias trigger during collisions at a centre-of-mass energy of 900 GeV. The charged-particle multiplicity, its dependence on transverse momentum and pseudorapidity. and the relationship between mean transverse momentum and charged-particle multiplicity are measured for events with at least one charged particle in the kinematic range vertical bar eta vertical bar < 2.5 and P-T > 500 MeV. The measurements are compared to Monte Carlo models of proton-proton collisions and to results from other experiments at the same centre-of-mass energy. The charged-particle multiplicity per event and unit of pseudorapidity eta = 0 is measured to be 1.333 +/- 0.003(stat.) +/- 0.040(syst.), which is 5-15% higher than the Monte Carlo models predict. (C) 2010 Published by Elsevier B.V.